Le concept de situation chez Paulo Freire : une perspective socio-anthropologique, culturelle et politique - Yves Lenoir; Arturo Ornelas Lizardi (Recherches en Éducation)
This article presents the conception of the notion of situation in the thought of Paulo Freire. Stressing the emancipatory aim pursued by this educator of international renown, the text draws on several of his writings to highlight the socio-anthropological, cultural, and political conception of the notion. After having distanced itself from various interpretations of Freire’s works which we judge to be simplistic, the text approaches the notion of situation by dissecting it so as to identify the educational process here conveyed. This educational process leads from the situation—existential, concrete, and anchored in the everydayness of life—to awareness requiring a dialectical task of scientific conceptualization via the “limit-situation” and the “problem-situation.” The article then offers up a comparison of the Freirian perspective with certain aspects of the conceptions of Bourdieu, Vygotsky, Brousseau, and Vergnaud in view of revealing common points or differences.